GAMBARAN ASUHAN KEPERAWATAN GAWAT DARURAT PADA PASIEN INFARK MIOKARD AKUT DENGAN NYERI AKUT DI RUANG EMERGENCY CARDIO RSUP SANGLAH DENPASAR - I Kadek Artawan; I.M.S Wijaya; L.A Arini; I.N Sunirda (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2019)
Background: Acute Myocardial Infarction (AMI) is one of the cardiovascular emergency diseases. Sign and symptoms of IMA that accompany patients coming to the Emergency departement are complaints of chest pain. Chest pain is a response that occurs due to ischemia in the myocardium. Untrained chest pain more than 20 minutes will result in irreversible heart damage. The purpose of this case study is to describe emergency nursing care in IMA patients with acute pain Method: The method used in this paper is a descriptive method with a case study approach that describes the condition of two patients suffering from IMA with acute pain. The tools used to retrieve data are IMA observation checklists and interview sheets. The data obtained were analyzed by narrating the data obtained and comparing the existing theory. Results: The IMA patient assessment focused on secondary assessment of SAMPLE. Chest pain data were obtained through the PQRST approach so that the main nursing problem was acute pain. Emergency measures performed by oxygen delivery as nonpharmacological therapy and administration of anti-ischaemic therapy and fibrinolysis as pharmacological therapy. Evaluation performed for 1 hour, the results obtained are reduced pain from the weight scale to moderate. Conclusions: As emergency nurses should pay attention to IMA assessment on secondary assessment and collaborate with medical personnel to reduce pain with pharmacological and nonpharmacological therapies.Keywords: Acute Myocardial Infarction (AMI); Acute Pain; Nursing Care; Emergency